High-performance all-solid-state electrolytic tank for producing hydrogen by electrolyzing water and preparation method of high-performance all-solid-state electrolytic tank

Through co-casting process and screen printing technology, combined with powder materials such as MxCe1-xNyO2 and LSCF, a high-performance all-solid-state electrolytic cell was prepared, which solved the isolation layer and oxygen electrode performance problems of existing electrolytic cells when running at high temperatures, and achieved efficient hydrogen production effect of water electrolytic and low energy consumption energy conversion.

CN119530829AActive Publication Date: 2025-02-28INNER MONGOLIA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411736533.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

When existing solid oxide electrolytic cells operate at high temperatures, there are problems with poor isolation layer performance, mutual diffusion reaction of oxygen electrodes, durability and stability, resulting in reduced Faraday effect and low efficiency of the electrolytic cells.

Method used

The half-cell was prepared by co-casting process, the isolation layer and oxygen electrode were prepared by screen printing technology, and powder materials such as MxCe1-xNyO2 and LSCF were used, and high-performance all-solid-state electrolytic cells were prepared in combination with high-temperature sintering technology.

Benefits of technology

It realizes efficient catalytic activity of electrolytic water hydrogen production and Faraday efficiency, reduces electricity consumption, improves energy conversion efficiency, and the material preparation process is economical, safe, green and environmentally friendly, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530829A_ABST
    Figure CN119530829A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance all-solid-state electrolytic tank for producing hydrogen by electrolyzing water and a preparation method of the high-performance all-solid-state electrolytic tank. The preparation method mainly comprises the following steps: preparation of electrode powder: preparing (La0. 6Sr0. 4) 0.95 Co0. 2Fe0. 8O3-delta (LSCF) powder by adopting a liquid-phase synthesis method, and preparing MxCe1-xNyO2 powder by adopting a coprecipitation method for an electrode and an isolating layer; preparing a half cell by adopting a co-casting process; an isolating layer and an oxygen electrode are prepared by adopting a silk-screen printing technology, and high-content water vapor is introduced to realize hydrogen production by electrolyzing water. The prepared high-performance all-solid-state electrolytic tank has efficient water electrolysis hydrogen production catalytic activity and Faraday efficiency, can operate at the medium-high temperature of 650-850 DEG C, and can effectively reduce electric energy consumption and improve energy conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrolytic cell, and in particular to a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolyzing water and a preparation method thereof. Background Art

[0002] At present, energy crisis and environmental pollution force energy transformation. Among them, hydrogen energy has the advantages of high calorific value and no pollution, which has attracted much attention from researchers. Hydrogen energy has risen to the national energy strategic position. The current methods of hydrogen production include fossil fuel hydrogen production, methanol reforming hydrogen production, industrial byproduct hydrogen production and water electrolysis hydrogen production. Among them, water electrolysis hydrogen production can be coupled with clean electricity such as solar energy, wind energy, and tidal energy for electrolysis, reducing the waste of excess electricity.

[0003] There are currently three main ways to produce hydrogen by electrolysis of water: alkaline water electrolyzer, proton exchange membrane electrolyzer and solid oxide electrolyzer (SOEC). First of all, alkaline water electrolysis technology is the most mature at present, but due to the large number of side reactions, the electrolysis efficiency is low, the electrolyte material is highly corrosive, and there are certain safety hazards. The proton exchange membrane electrolyzer is a new pollution-free technology, but because it uses precious metals as electrode materials, the equipment cost is relatively high. In comparison, SOEC can operate at a high temperature of 650-850℃. It is an energy storage device that converts electrical energy and thermal energy into chemical energy, which can effectively reduce electricity consumption and improve energy conversion efficiency. Therefore, the production of hydrogen by electrolysis of water by SOEC is of great significance to the reform of new energy and the better realization of the "dual carbon goals".

[0004] Solid oxide electrolysis cells (SOECs) generally include hydrogen electrodes, electrolytes, isolation layers, and oxygen electrodes. The performance of the isolation layer seriously affects the performance of the electrolysis cell. Too high or too low sintering temperatures lead to excessive ohmic resistance of the battery, resulting in a reduction in the Faraday effect of the electrolysis cell. The performance of the oxygen electrode seriously affects the efficiency and durability of the electrolysis cell. During the long-term operation of the electrolysis cell, the oxygen electrode has problems such as mutual diffusion reactions, durability, and stability caused by high temperatures, which seriously hinder the long-term stability of the electrolysis cell. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water. The high-performance all-solid-state electrolytic cell prepared by the present invention has high-efficiency catalytic activity and Faraday efficiency for producing hydrogen by electrolysis of water, can operate at medium and high temperatures of 650-850°C, can effectively reduce electricity consumption, and improve energy conversion efficiency.

[0006] In order to solve the above technical problems, the technical solution of the present invention is:

[0007] A method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolyzing water comprises the following steps:

[0008] S1. NiO, YSZ and organic glue solution are mixed, ball-milled for 12-24 hours, and then co-cast to form a support layer and a hydrogen electrode, and the hydrogen electrode is disposed on the support layer;

[0009] S2. YSZ and organic glue are mixed evenly to obtain YSZ slurry, the YSZ slurry is screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer, and sintered at high temperature for 2-5h to obtain a half-cell;

[0010] S3. According to M x Ce 1-x N y Stoichiometric ratio of O2: Inorganic salts of M, Ce, and N elements are weighed and dissolved in deionized water, and PVP is added and mixed to obtain a mixed solution A, wherein M = Pr, La, Nd, Sm or Gd, N = Fe, Mn, Cu, Co, Ni or Zn, 0≤x≤0.3, 0≤y≤0.1;

[0011] S4. The precipitant was dissolved in deionized water, mixed to obtain a mixed solution B, and the mixed solution A obtained in step S3 was added dropwise to the mixed solution B under stirring, and stirring was continued for 2-4h after the addition was completed. After stopping stirring, aging was continued for 12-24h to obtain a reactant;

[0012] S5. The reaction product obtained in step S4 is centrifuged to obtain a precipitate, the precipitate is washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate is dried and calcined at high temperature for 2-5h to obtain M x Ce 1-x N y O2 powder;

[0013] S6. The M obtained in step S5 is x Ce 1-x N y O2 powder and organic glue are uniformly mixed to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer;

[0014] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ Inorganic salts of La, Sr, Co, and Fe are weighed and dissolved in deionized water in a stoichiometric ratio, glycine is added and heated to a gel state, and then sintered in a muffle furnace at high temperature for 2-5 hours to obtain LSCF oxygen electrode powder;

[0015] S8. The M obtained in step S5 is x Ce 1-x Ny O2 powder, LSCF oxygen electrode powder obtained in step S7, and organic glue are evenly mixed to obtain oxygen electrode slurry, and the oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode, and sintered at high temperature for 1-3 hours to obtain a high-performance all-solid-state electrolytic cell for electrolyzing water to produce hydrogen.

[0016] Furthermore, in step S1 of the present invention, the organic glue solution is composed of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral and PEG, and the weight ratio of NiO, YSZ and organic glue solution is 6:4:(2-5); the speed of the ball mill is 100-500r / min; the thickness of the support layer is 300-1000μm, and the thickness of the hydrogen electrode is 10-50μm. Among them, the support layer is the basis of the electrolytic cell and has a certain thickness to provide sufficient structural strength to ensure that the battery does not deform or even break under various stresses; the hydrogen electrode is the reaction site where water vapor molecules obtain electrons to undergo reduction reaction to generate oxygen ions and hydrogen molecules, and is closely connected to the electrolyte layer.

[0017] Furthermore, in step S2 of the present invention, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of (1-5):50, and the weight ratio of YSZ to organic glue is 1:(1-5); the temperature of high temperature calcination is 1200-1400°C; and the thickness of the electrolyte layer is 0.01-0.02mm. The electrolyte layer is a multifunctional region that separates the hydrogen electrode and the oxygen electrode and is responsible for carrying oxygen ions and blocking electron conduction.

[0018] Furthermore, in step S3 of the present invention, M x Ce 1-x N y The ratio of O2, deionized water and PVP is 1 mol:(1-2)L:(0.1-0.2)g, and the inorganic salt of M, Ce and N elements is one of nitrates, acetates or chlorides of M, Ce and N elements.

[0019] Furthermore, in step S4 of the present invention, the ratio of the precipitant to deionized water is (0.1-0.75) mol:1L, the precipitant is one of ammonium carbonate, urea, ammonium oxalate or ammonia water; the volume ratio of the mixed solution A and the mixed solution B is 1:(2-3); the dropping speed of the mixed solution A is 5-10 mL / min; and the stirring speed is 300-500 r / min.

[0020] Furthermore, in step S5 of the present invention, the centrifugal speed is 10000 rpm, the time is 20 min; the drying temperature is 100-120° C., the time is 10-12 h; and the high-temperature calcination temperature is 600-800° C.

[0021] Furthermore, in step S6 of the present invention, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of (1-5):25, M x Ce 1-x N y The weight ratio of O2 powder and organic glue is 1:(1-2), and the thickness of the isolation layer is 1-5μm. The isolation layer is an isolation zone that prevents the oxygen electrode from directly contacting the electrolyte and inhibits the diffusion of some elements in the oxygen electrode, and has good ionic conductivity.

[0022] Furthermore, in step S7 of the present invention, (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol; the inorganic salt of La, Sr, Co, and Fe elements is one of the nitrates, acetates, or chlorides of La, Sr, Co, and Fe elements; the heating temperature is 80-300°C; and the high-temperature sintering temperature is 300-600°C.

[0023] Furthermore, in step S8 of the present invention, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of (1-5):25, M x Ce 1-x N y The weight ratio of O2 powder, LSCF oxygen electrode powder and organic glue is (1-2):1:1, the high temperature sintering temperature is 1000-1200℃; the thickness of the oxygen electrode is 10-30μm. The oxygen electrode is the reaction site where oxygen ions lose electrons to undergo oxidation reaction and precipitate oxygen molecules.

[0024] Another technical problem to be solved by the present invention is to provide a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolyzing water, which is prepared by the above preparation method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) The raw materials used in the present invention are economical and safe, and the material preparation process is green and environmentally friendly.

[0027] 2) In the present invention, the main materials used in the all-solid-state high-temperature electrolytic cell, such as rare earth oxide M x Ce 1-x N y O2 (M=Pr, La, Nd, Sm, Gd; N=Fe, Mn, Cu, Co, Ni, Zn; 0≤x≤0.3; 0≤y≤0.1) and (La 0.6 Sr 0.4 ) 0.95 Co 0.2Fe 0.8 O 3-δ Powder materials such as (LSCF) can be synthesized through simple co-precipitation and combustion methods, which are low-cost, environmentally friendly, and suitable for large-scale production.

[0028] 3) The present invention adopts a co-casting process to prepare a half-cell, and a screen printing technology to prepare an isolation layer and an oxygen electrode. The structure of the all-solid-state electrolytic cell assembly is stable, the process is simple, and the cost is low. After high-temperature sintering, it has a density of about 95%, and can achieve better electrolytic cell performance in a wider range of operating temperatures.

[0029] 4) The all-solid-state high-temperature electrolytic cell prepared by the present invention has excellent electrochemical performance, and the rare earth M x Ce 1-x N y O2 oxide exhibits high ionic conductivity at medium and high temperatures, which facilitates ion transport and reduces battery internal resistance. As a composite electrode, it can increase the ion transport rate at the electrode three-phase interface, enhance the interfacial charge transfer process of the electrode, improve the electrochemical properties of the oxygen electrode and the fuel electrode, and ultimately achieve efficient all-solid-state electrolytic cell performance.

[0030] 5) The all-solid-state electrolytic cell prepared by the present invention is sealed on a ceramic tube, and water vapor of different contents is introduced and voltage is applied to achieve the preparation of hydrogen. The present invention can efficiently convert electrical energy and thermal energy into chemical energy, that is, electrolyze water vapor into hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 (a) is the LSCF oxygen electrode powder prepared in Example 1 of the present invention, M x Ce 1-x N y X-ray powder diffraction pattern (XRD) of O2 powder; Figure 1 (b) LSCF oxygen electrode powder, M x Ce 1-x N y X-ray diffraction patterns of O2 powders uniformly mixed in different proportions and calcined at 1100℃ for 2h;

[0033] Figure 2 The LSCF oxygen electrode powder and M prepared in different proportions are x Ce 1-x N y(a) Nyquist spectrum, (b) polarization resistance, Arrhenius curve (c) Rp, (d) Ro of the oxygen electrode composited with O2 powder under 700 and 800℃ test;

[0034] Figure 3 The graph is a water electrolysis performance diagram of oxygen electrodes with different proportions and components prepared in the present invention. DETAILED DESCRIPTION

[0035] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0036] Example 1

[0037] A high-performance all-solid-state electrolyzer for hydrogen production by water electrolysis was prepared as follows:

[0038] S1. NiO, YSZ, and an organic glue solution were mixed in a weight ratio of 6:4:4, wherein the organic glue solution consisted of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate, and PEG, and after ball milling at a speed of 300 r / min for 18 h, a support layer with a thickness of 1000 μm and a hydrogen electrode with a thickness of 20 μm were prepared by co-casting, and the hydrogen electrode was disposed on the support layer;

[0039] S2. YSZ and organic glue were mixed uniformly in a weight ratio of 1:1 to obtain a YSZ slurry, wherein the organic glue was composed of ethyl cellulose and pinene alcohol in a weight ratio of 3:50, and the YSZ slurry was screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer with a thickness of 0.02 mm, and sintered at a high temperature of 1400°C for 5h to obtain a half-cell;

[0040] S3. According to M x Ce 1-x N y The nitrate of the M element, the nitrate of the Ce element, and the nitrate of the N element were weighed and dissolved in deionized water, and PVP was added and mixed to obtain a mixed solution A, M x Ce 1-x N y The ratio of O2, deionized water, and PVP is 1 mol:1 L:0.2 g, wherein M=Sm, N=Mn, x=0.15, y=0.075, the nitrate of Sm element is Sm(NO3)3·6H2O, the nitrate of Ce element is Ce(NO3)3·6H2O, and the nitrate of Mn element is Mn(NO3)4·4H2O;

[0041] S4. Dissolve ammonium carbonate in deionized water at a ratio of 0.75 mol: 1 L, mix well to obtain a mixed solution B, and add the mixed solution A obtained in step S3 to the mixed solution B at a volume ratio of 1: 2 under stirring at a dropping speed of 10 mL / min. After the dropping is completed, continue stirring at a speed of 400 r / min for 4 h, stop stirring and continue aging for 12 h to obtain a reactant;

[0042] S5. The reaction product obtained in step S4 was centrifuged at 10000 rpm for 20 min to obtain a precipitate, the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate was dried at 115 ° C for 12 h and then calcined at 700 ° C for 2 h to obtain M x Ce 1-x N y O2 powder, denoted as Mn-SDC powder;

[0043] S6. The Mn-SDC powder obtained in step S5 is mixed with an organic glue in a weight ratio of 1:1 to obtain an isolation layer slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:25, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer with a thickness of 3 μm;

[0044] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ The nitrate of La, Sr, Co and Fe in a stoichiometric ratio were weighed and dissolved in deionized water. After adding glycine, they were heated at 200°C until they were in a gel state. 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol, and then sintered in a muffle furnace at 300°C for 2 h to obtain LSCF oxygen electrode powder, wherein the nitrate of the La element is La(NO3)3·9H2O, the nitrate of the Sr element is Sr(NO3)2, the nitrate of the Co element is Co(NO3)2·6H2O, and the nitrate of the Fe element is Fe(NO3)3·9H2O;

[0045] S8. The Mn-SDC powder obtained in step S5, the LSCF oxygen electrode powder obtained in step S7, and the organic glue are mixed evenly in a weight ratio of 1:1:1 to obtain oxygen electrode slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:25. The oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode with a thickness of 20 μm. The oxygen electrode is sintered at a high temperature of 1150°C for 2 hours to obtain a high-performance all-solid-state electrolytic cell for electrolyzing water to produce hydrogen.

[0046] The high-performance all-solid-state electrolytic cell prepared in Example 1 is sealed on an alumina tube, then placed in a resistance furnace and heated to 650-850° C., and voltage is applied simultaneously through water at different temperatures to precipitate hydrogen on the surface of the hydrogen electrode.

[0047] Example 2

[0048] A high-performance all-solid-state electrolyzer for hydrogen production by water electrolysis was prepared as follows:

[0049] S1. NiO, YSZ, and an organic glue solution were mixed in a weight ratio of 6:4:3, wherein the organic glue solution consisted of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate, and PEG, and after ball milling at a speed of 200 r / min for 21 h, a support layer with a thickness of 800 μm and a hydrogen electrode with a thickness of 30 μm were prepared by co-casting, and the hydrogen electrode was disposed on the support layer;

[0050] S2. YSZ and organic glue were mixed uniformly in a weight ratio of 1:5 to obtain a YSZ slurry, wherein the organic glue was composed of ethyl cellulose and pinene alcohol in a weight ratio of 5:50, and the YSZ slurry was screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer with a thickness of 0.01 mm, and sintered at a high temperature of 1300°C for 4h to obtain a half-cell;

[0051] S3. According to M x Ce 1-x N y The nitrate of the M element, the nitrate of the Ce element, and the nitrate of the N element were weighed and dissolved in deionized water, and PVP was added and mixed to obtain a mixed solution A, M x Ce 1-x N y The ratio of O2, deionized water, and PVP is 1 mol:2L:0.2g, wherein M=Sm, N=Mn, x=0.15, y=0.075, the nitrate of Sm element is Sm(NO3)3·6H2O, the nitrate of Ce element is Ce(NO3)3·6H2O, and the nitrate of Mn element is Mn(NO3)4·4H2O;

[0052] S4. Dissolve ammonium carbonate in deionized water at a ratio of 0.1 mol: 1 L, mix well to obtain a mixed solution B, and add the mixed solution A obtained in step S3 to the mixed solution B at a volume ratio of 1: 2 under stirring at a dropping speed of 8 mL / min. After the dripping, continue stirring at a speed of 300 r / min for 3 h, stop stirring and continue aging for 24 h to obtain a reactant;

[0053] S5. The reaction product obtained in step S4 was centrifuged at 10000 rpm for 20 min to obtain a precipitate, the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate was dried at 100 ° C for 10 h and then calcined at 650 ° C for 4 h to obtain M x Ce 1-x N y O2 powder, denoted as Mn-SDC powder;

[0054] S6. The Mn-SDC powder obtained in step S5 is mixed with an organic glue in a weight ratio of 1:2 to obtain an isolation layer slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 2:25, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer with a thickness of 4 μm;

[0055] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ The nitrate of La, Sr, Co and Fe in a stoichiometric ratio were weighed and dissolved in deionized water. After adding glycine, they were heated at 200°C until they were in a gel state. 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol, and then sintered at 400°C in a muffle furnace for 3 h to obtain LSCF oxygen electrode powder, wherein the nitrate of the La element is La(NO3)3·9H2O, the nitrate of the Sr element is Sr(NO3)2, the nitrate of the Co element is Co(NO3)2·6H2O, and the nitrate of the Fe element is Fe(NO3)3·9H2O;

[0056] S8. The Mn-SDC powder obtained in step S5, the LSCF oxygen electrode powder obtained in step S7, and the organic glue are mixed evenly in a weight ratio of 1.5:1:1 to obtain oxygen electrode slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 2:25. The oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode with a thickness of 15 μm. The oxygen electrode is sintered at a high temperature of 1200°C for 2 hours to obtain a high-performance all-solid-state electrolytic cell for electrolyzing water to produce hydrogen.

[0057] The high-performance all-solid-state electrolytic cell prepared in Example 2 is sealed on an alumina tube, then placed in a resistance furnace and heated to 650-850°C, and voltage is applied simultaneously through water at different temperatures to precipitate hydrogen on the surface of the hydrogen electrode.

[0058] Example 3

[0059] A high-performance all-solid-state electrolyzer for hydrogen production by water electrolysis was prepared as follows:

[0060] S1. NiO, YSZ, and an organic glue solution were mixed in a weight ratio of 6:4:2, wherein the organic glue solution consisted of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate, and PEG, and after ball milling at a speed of 400 r / min for 15 h, a support layer with a thickness of 500 μm and a hydrogen electrode with a thickness of 10 μm were prepared by co-casting, and the hydrogen electrode was disposed on the support layer;

[0061] S2. YSZ and organic glue are mixed uniformly in a weight ratio of 1:3 to obtain a YSZ slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:50, and the YSZ slurry is screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer with a thickness of 0.01 mm, and sintered at a high temperature of 1200°C for 5h to obtain a half-cell;

[0062] S3. According to M x Ce 1-x N y The nitrate of the M element, the nitrate of the Ce element, and the nitrate of the N element were weighed and dissolved in deionized water, and PVP was added and mixed to obtain a mixed solution A, M x Ce 1-x N y The ratio of O2, deionized water, and PVP is 1 mol:1 L:0.1 g, wherein M=Pr, N=Mn, x=0.3, y=0.05, the nitrate of the Pr element is Pr(NO3)3·6H2O, the nitrate of the Ce element is Ce(NO3)3·6H2O, and the nitrate of the Mn element is Mn(NO3)4·4H2O;

[0063] S4. Dissolve ammonium carbonate in deionized water at a ratio of 0.2 mol: 1 L, mix well to obtain a mixed solution B, and add the mixed solution A obtained in step S3 to the mixed solution B at a volume ratio of 1: 3 under stirring at a dropping speed of 5 mL / min. After the dripping, continue stirring at a speed of 500 r / min for 2 h, stop stirring and continue aging for 18 h to obtain a reactant;

[0064] S5. The reaction product obtained in step S4 was centrifuged at 10000 rpm for 20 min to obtain a precipitate, the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate was dried at 120 ° C for 11 h and then calcined at 800 ° C for 5 h to obtain M x Ce 1-x N y O2 powder, denoted as Mn-PDC powder;

[0065] S6. The Mn-PDC powder obtained in step S5 is mixed with an organic glue in a weight ratio of 1:1 to obtain an isolation layer slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 5:25, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer with a thickness of 2 μm;

[0066] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ The nitrates of La, Sr, Co and Fe were weighed in a stoichiometric ratio and dissolved in deionized water. After adding glycine, they were heated at 100°C until they were in a gel state. 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol, and then sintered at 600°C in a muffle furnace for 2 h to obtain LSCF oxygen electrode powder, wherein the nitrate of the La element is La(NO3)3·9H2O, the nitrate of the Sr element is Sr(NO3)2, the nitrate of the Co element is Co(NO3)2·6H2O, and the nitrate of the Fe element is Fe(NO3)3·9H2O;

[0067] S8. The Mn-PDC powder obtained in step S5, the LSCF oxygen electrode powder obtained in step S7, and the organic glue are mixed evenly in a weight ratio of 1:1:1 to obtain oxygen electrode slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 5:25. The oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode with a thickness of 10 μm. The oxygen electrode is sintered at a high temperature of 1100°C for 2.5 hours to obtain a high-performance all-solid-state electrolytic cell for hydrogen production by electrolysis of water.

[0068] The high-performance all-solid-state electrolytic cell prepared in Example 3 is sealed on an alumina tube, then placed in a resistance furnace and heated to 650-850°C, and voltage is applied simultaneously through water at different temperatures to precipitate hydrogen on the surface of the hydrogen electrode.

[0069] Example 4

[0070] A high-performance all-solid-state electrolyzer for hydrogen production by water electrolysis was prepared as follows:

[0071] S1. NiO, YSZ and an organic glue solution were mixed in a weight ratio of 6:4:5, wherein the organic glue solution consisted of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate and PEG in equal weights, and after ball milling at a speed of 100 r / min for 24 h, a support layer with a thickness of 300 μm and a hydrogen electrode with a thickness of 10 μm were prepared by co-casting, and the hydrogen electrode was disposed on the support layer;

[0072] S2. YSZ and organic glue are mixed uniformly in a weight ratio of 1:2 to obtain a YSZ slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 4:50, and the YSZ slurry is screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer with a thickness of 0.02 mm, and sintered at a high temperature of 1250°C for 4h to obtain a half-cell;

[0073] S3. According to M x Ce 1-x N y The nitrate of the M element, the nitrate of the Ce element, and the nitrate of the N element were weighed and dissolved in deionized water, and PVP was added and mixed to obtain a mixed solution A, M x Ce 1-x N y The ratio of O2, deionized water, and PVP is 1 mol:2L:0.1 g, wherein M=Pr, N=Co, x=0.25, y=0.025, the nitrate of the Pr element is Pr(NO3)3·6H2O, the nitrate of the Ce element is Ce(NO3)3·6H2O, and the nitrate of the Co element is Co(NO3)4·6H2O;

[0074] S4. Dissolve ammonium carbonate in deionized water at a ratio of 0.5 mol: 1 L, mix well to obtain a mixed solution B, and add the mixed solution A obtained in step S3 to the mixed solution B at a volume ratio of 1: 3 under stirring at a dropping speed of 10 mL / min. After the dripping, continue stirring at a speed of 400 r / min for 3 h, stop stirring and continue aging for 12 h to obtain a reactant;

[0075] S5. The reaction product obtained in step S4 was centrifuged at 10000 rpm for 20 min to obtain a precipitate, the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate was dried at 110 ° C for 10 h and then calcined at 650 ° C for 3.5 h to obtain M x Ce 1-x N y O2 powder, denoted as Co-PDC powder;

[0076] S6. The Co-PDC powder obtained in step S5 is mixed with an organic glue in a weight ratio of 1:1 to obtain an isolation layer slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 4:25, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer with a thickness of 1 μm;

[0077] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ The nitrates of La, Sr, Co and Fe were weighed in a stoichiometric ratio and dissolved in deionized water. After adding glycine, they were heated at 80°C until they were in a gel state. (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1 L:2 mol, and then sintered in a muffle furnace at 350°C for 4 h to obtain LSCF oxygen electrode powder, wherein the nitrate of the La element is La(NO3)3·9H2O, the nitrate of the Sr element is Sr(NO3)2, the nitrate of the Co element is Co(NO3)2·6H2O, and the nitrate of the Fe element is Fe(NO3)3·9H2O;

[0078] S8. The Co-PDC powder obtained in step S5, the LSCF oxygen electrode powder obtained in step S7, and the organic glue are mixed evenly in a weight ratio of 1:1:1 to obtain oxygen electrode slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 4:25. The oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode with a thickness of 15 μm. The oxygen electrode is sintered at a high temperature of 1000°C for 3 hours to obtain a high-performance all-solid-state electrolyzer for hydrogen production by electrolysis of water.

[0079] The high-performance all-solid-state electrolytic cell prepared in Example 4 is sealed on an alumina tube, then placed in a resistance furnace and heated to 650-850°C, and voltage is applied simultaneously through water at different temperatures to precipitate hydrogen on the surface of the hydrogen electrode.

[0080] Example 5

[0081] A high-performance all-solid-state electrolyzer for hydrogen production by water electrolysis was prepared as follows:

[0082] S1. NiO, YSZ, and an organic glue solution were mixed in a weight ratio of 6:4:3, wherein the organic glue solution consisted of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate, and PEG, and after ball milling at a speed of 500 r / min for 12 h, a support layer with a thickness of 400 μm and a hydrogen electrode with a thickness of 50 μm were prepared by co-casting, and the hydrogen electrode was disposed on the support layer;

[0083] S2. YSZ and organic glue are mixed uniformly in a weight ratio of 1:4 to obtain a YSZ slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 2:50, and the YSZ slurry is screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer with a thickness of 0.01 mm, and sintered at a high temperature of 1350°C for 4h to obtain a half-cell;

[0084] S3. According to M x Ce 1-x N y The nitrate of the M element, the nitrate of the Ce element, and the nitrate of the N element were weighed and dissolved in deionized water, and PVP was added and mixed to obtain a mixed solution A, M x Ce 1-x N y The ratio of O2, deionized water, and PVP is 1 mol:1.5 L:0.1 g, where M=Nd, N=Fe, x=0.1, y=0.08, the nitrate of Nd element is Nd(NO3)3·6H2O, the nitrate of Ce element is Ce(NO3)3·6H2O, and the nitrate of Fe element is Fe(NO3)4·9H2O;

[0085] S4. Dissolve ammonium carbonate in deionized water at a ratio of 0.4 mol: 1 L, mix well to obtain a mixed solution B, and add the mixed solution A obtained in step S3 to the mixed solution B at a volume ratio of 1: 2 under stirring at a dropping speed of 5 mL / min. After the dropping is completed, continue stirring at a speed of 500 r / min for 4 h, stop stirring and continue aging for 21 h to obtain a reactant;

[0086] S5. The reaction product obtained in step S4 was centrifuged at 10000 rpm for 20 min to obtain a precipitate, the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate was dried at 120 ° C for 10.5 h and then calcined at 750 ° C for 3 h to obtain M x Ce 1-x N y O2 powder, denoted as Fe-NDC powder;

[0087] S6. The Fe-NDC powder obtained in step S5 is mixed with an organic glue in a weight ratio of 1:2 to obtain an isolation layer slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 3:25, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer with a thickness of 5 μm;

[0088] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ The nitrate of La, Sr, Co and Fe in a stoichiometric ratio were weighed and dissolved in deionized water. After adding glycine, they were heated at 250°C until they were in a gel state. 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol, and then sintered in a muffle furnace at 500°C for 2.5 h to obtain LSCF oxygen electrode powder, wherein the nitrate of the La element is La(NO3)3·9H2O, the nitrate of the Sr element is Sr(NO3)2, the nitrate of the Co element is Co(NO3)2·6H2O, and the nitrate of the Fe element is Fe(NO3)3·9H2O;

[0089] S8. The Fe-NDC powder obtained in step S5, the LSCF oxygen electrode powder obtained in step S7, and the organic glue are mixed evenly in a weight ratio of 1:1:1 to obtain oxygen electrode slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 3:25. The oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode with a thickness of 25 μm. The oxygen electrode is sintered at a high temperature of 1050°C for 1.5 h to obtain a high-performance all-solid-state electrolytic cell for hydrogen production by electrolysis of water.

[0090] The high-performance all-solid-state electrolytic cell prepared in Example 5 is sealed on an alumina tube, then placed in a resistance furnace and heated to 650-850°C, and voltage is applied simultaneously through water at different temperatures to precipitate hydrogen on the surface of the hydrogen electrode.

[0091] Example 6

[0092] A high-performance all-solid-state electrolyzer for hydrogen production by water electrolysis was prepared as follows:

[0093] S1. NiO, YSZ, and an organic glue solution were mixed in a weight ratio of 6:4:4, wherein the organic glue solution consisted of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate, and PEG, and after ball milling at a speed of 200 r / min for 24 h, a support layer with a thickness of 600 μm and a hydrogen electrode with a thickness of 40 μm were prepared by co-casting, and the hydrogen electrode was disposed on the support layer;

[0094] S2. YSZ and organic glue were mixed uniformly in a weight ratio of 1:3 to obtain a YSZ slurry, wherein the organic glue was composed of ethyl cellulose and pinene alcohol in a weight ratio of 3:50, and the YSZ slurry was screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer with a thickness of 0.02 mm, and sintered at a high temperature of 1400°C for 3h to obtain a half-cell;

[0095] S3. According to M x Ce 1-x N y The nitrate of the M element, the nitrate of the Ce element, and the nitrate of the N element were weighed and dissolved in deionized water, and PVP was added and mixed to obtain a mixed solution A, M x Ce 1-x N y The ratio of O2, deionized water, and PVP is 1 mol:1.5 L:0.2 g, wherein M=Nd, N=Mn, x=0.15, y=0.06, the nitrate of Nd element is Nd(NO3)3·6H2O, the nitrate of Ce element is Ce(NO3)3·6H2O, and the nitrate of Mn element is Mn(NO3)3·9H2O;

[0096] S4. Dissolve ammonium carbonate in deionized water at a ratio of 0.3 mol: 1 L, mix well to obtain a mixed solution B, and add the mixed solution A obtained in step S3 to the mixed solution B at a volume ratio of 1: 3 under stirring at a dropping speed of 10 mL / min. After the dripping, continue stirring at a speed of 300 r / min for 3 h, stop stirring and continue aging for 15 h to obtain a reactant;

[0097] S5. The reaction product obtained in step S4 was centrifuged at 10000 rpm for 20 min to obtain a precipitate, the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate was dried at 110 ° C for 11.5 h and then calcined at 700 ° C for 2.5 h to obtain M x Ce 1-x N y O2 powder, recorded as Mn-NDC powder;

[0098] S6. The Mn-NDC powder obtained in step S5 is mixed with an organic glue in a weight ratio of 1:2 to obtain an isolation layer slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 2:25, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer with a thickness of 3 μm;

[0099] S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ The nitrates of La, Sr, Co and Fe were weighed and dissolved in deionized water in a stoichiometric ratio. After adding glycine, they were heated at 150°C until they were in a gel state. 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol, and then sintered in a muffle furnace at 450°C for 5 h to obtain LSCF oxygen electrode powder, wherein the nitrate of La element is La(NO3)3·9H2O, the nitrate of Sr element is Sr(NO3)2, the nitrate of Co element is Co(NO3)2·6H2O, and the nitrate of Fe element is Fe(NO3)3·9H2O;

[0100] S8. The Mn-NDC powder obtained in step S5, the LSCF oxygen electrode powder obtained in step S7, and the organic glue are mixed evenly in a weight ratio of 2:1:1 to obtain oxygen electrode slurry, wherein the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 4:25. The oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode with a thickness of 30 μm. The oxygen electrode is sintered at a high temperature of 1150°C for 2 hours to obtain a high-performance all-solid-state electrolytic cell for electrolyzing water to produce hydrogen.

[0101] The high-performance all-solid-state electrolytic cell prepared in Example 6 is sealed on an alumina tube, then placed in a resistance furnace and heated to 650-850°C, and voltage is applied simultaneously through water at different temperatures to precipitate hydrogen on the surface of the hydrogen electrode.

[0102] Comparative Example 1:

[0103] The difference from Example 1 is that Mn(NO3)4·4H2O is not used in step S3, and SDC powder is obtained in step S5.

[0104] The difference from Example 1 is that Mn(NO3)4·4H2O is not used in step S3, SDC powder is prepared in step S5, and in step S8, the weight ratio of SDC powder to LSCF oxygen electrode powder is 1.5:1.

[0105] Comparative Example 3:

[0106] The difference from Example 1 is that no Mn-SDC powder is used in step S8.

[0107] Experimental example

[0108] The polarization resistance and water electrolysis hydrogen production performance of the electrolytic cells prepared in Examples 1-6 and Comparative Examples 1-3 were respectively measured in accordance with GB / T 34582-2017. The test results are shown in Table 1.

[0109]

[0110] Table 1

[0111] It can be seen from Table 1 that the polarization resistance and water electrolysis hydrogen production performance of Examples 1-6 of the present invention are better than those of Comparative Example 3. Some of the raw materials and preparation steps used in Comparative Examples 1-2 are different from those in Example 1. Compared with Example 1, the water electrolysis hydrogen production performance of Comparative Examples 1-2 is significantly reduced, indicating that the isolation layer and oxygen electrode used in the present invention can effectively improve the water electrolysis hydrogen production performance of the all-solid-state electrolytic cell at medium and high temperatures.

[0112] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water, characterized in that: The following steps are involved: S1. NiO, YSZ and organic glue solution are mixed, ball-milled for 12-24 hours, and then co-cast to form a support layer and a hydrogen electrode, and the hydrogen electrode is disposed on the support layer; S2. YSZ and organic glue are mixed evenly to obtain YSZ slurry, the YSZ slurry is screen-printed on the hydrogen electrode obtained in step S1 to form an electrolyte layer, and sintered at high temperature for 2-5h to obtain a half-cell; S3. According to M x Ce 1-x N y Stoichiometric ratio of O2: Inorganic salts of M, Ce, and N elements are weighed and dissolved in deionized water, and PVP is added and mixed to obtain a mixed solution A, wherein M = Pr, La, Nd, Sm or Gd, N = Fe, Mn, Cu, Co, Ni or Zn, 0≤x≤0.3, 0≤y≤0.1; S4. The precipitant was dissolved in deionized water, mixed to obtain a mixed solution B, and the mixed solution A obtained in step S3 was added dropwise to the mixed solution B under stirring, and stirring was continued for 2-4h after the addition was completed. After stopping stirring, aging was continued for 12-24h to obtain a reactant; S5. The reaction product obtained in step S4 is centrifuged to obtain a precipitate, the precipitate is washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, the precipitate is dried and calcined at high temperature for 2-5h to obtain M x Ce 1-x N y O2 powder; S6. The M obtained in step S5 is x Ce 1-x N y O2 powder and organic glue are uniformly mixed to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the surface of the hydrogen electrode of the half-cell obtained in step S2 to form an isolation layer; S7. According to (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ Inorganic salts of La, Sr, Co, and Fe are weighed and dissolved in deionized water in a stoichiometric ratio, glycine is added and heated to a gel state, and then sintered in a muffle furnace at high temperature for 2-5 hours to obtain LSCF oxygen electrode powder; S8. The M obtained in step S5 is x Ce 1-x N y O2 powder, LSCF oxygen electrode powder obtained in step S7, and organic glue are evenly mixed to obtain oxygen electrode slurry, and the oxygen electrode slurry is screen-printed on the surface of the isolation layer obtained in step S6 to form an oxygen electrode, and sintered at high temperature for 1-3 hours to obtain a high-performance all-solid-state electrolytic cell for electrolyzing water to produce hydrogen.

2. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In the step S1, the organic glue solution is composed of equal weights of ethanol, xylene, triethanolamine, castor oil, polyvinyl butyral, polymethyl acrylate and PEG, and the weight ratio of NiO, YSZ and organic glue solution is 6:4:(2-5); the rotation speed of the ball mill is 100-500r / min; the thickness of the support layer is 300-1000μm, and the thickness of the hydrogen electrode is 20-50μm.

3. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In the step S2, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of (1-5):50, and the weight ratio of YSZ and organic glue is 1:(1-5); the temperature of high-temperature calcination is 1200-1400°C; and the thickness of the electrolyte layer is 0.01-0.02mm.

4. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In step S3, M x Ce 1-x N y The ratio of O2, deionized water and PVP is 1 mol:(1-2)L:(0.1-0.2)g, and the inorganic salt of M, Ce and N elements is one of nitrates, acetates or chlorides of M, Ce and N elements.

5. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In step S4, the ratio of the precipitant to deionized water is (0.1-0.75) mol:1L, the precipitant is one of ammonium carbonate, urea, ammonium oxalate or ammonia water; the volume ratio of the mixed solution A to the mixed solution B is 1:(2-3); the dropping speed of the mixed solution A is 5-10 mL / min; and the stirring speed is 300-500 r / min.

6. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In step S5, the centrifugal speed is 10000 rpm, the time is 20 min; the drying temperature is 100-120° C., the time is 10-12 h; the high temperature calcination temperature is 600-800° C.

7. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In step S6, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of (1-5):25, x Ce 1- x N y The weight ratio of O2 powder and organic glue is 1:(1-2), and the thickness of the isolation layer is 1-5μm.

8. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In step S7, (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ , deionized water, and glycine in a ratio of 1 mol:1L:2 mol; the inorganic salt of La, Sr, Co, and Fe elements is one of the nitrates, acetates, or chlorides of La, Sr, Co, and Fe elements; the heating temperature is 80-300°C; and the high-temperature sintering temperature is 300-600°C.

9. The method for preparing a high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water according to claim 1, characterized in that: In step S8, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of (1-5):25, M x Ce 1- x N y The weight ratio of O2 powder, LSCF oxygen electrode powder and organic glue is (1-2):1:1, the high temperature sintering temperature is 1000-1200°C; the thickness of the oxygen electrode is 10-30μm.

10. A high-performance all-solid-state electrolytic cell for producing hydrogen by electrolysis of water, prepared according to the preparation method of claims 1 to 9.

Citation Information

Patent Citations

  • Novel high-temperature CO2 and H2O co-electrolysis superlattice composite oxygen electrode and preparation method thereof

    CN103296286A

  • Preparation method of solid oxide electrode material having ordered 3D micro-channel structure

    CN108448118A

  • Oxygen electrode slurry of solid oxide electrolytic cell, preparation method of oxygen electrode slurry and solid oxide electrolytic cell

    CN111962098A

  • Carbon dioxide conversion electrolytic tank as well as preparation method and application thereof

    CN113430548A

Cited By

  • Rare earth solid electrolytic tank for high-temperature water electrolysis hydrogen production and preparation method of rare earth solid electrolytic tank

    CN121006558A

  • All-solid-state electrolytic cell electrolytic catalytic material as well as preparation method and application thereof

    CN121874853A